On local H∞ switched controller design for uncertain T–S fuzzy systems subject to actuator saturation with unknown membership functions - de Oliveira, Diogo Ramalho [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Alves, Uiliam Nelson Lendzion Tomaz; de Souza, Wallysonn Alves; Assunção, Edvaldo [UNESP]; Cardim, Rodrigo [UNESP] (Elsevier, 2018)
This manuscript proposes a local H∞ switched controller design for a class of uncertain nonlinear plants described by Takagi–Sugeno (T–S) fuzzy models with unknown membership functions. The control design requires only the lower and upper bounds of the system nonlinearities and of the system linear parameters, which can depend on uncertain parameters. The switched control law chooses a state-feedback controller gain, which belongs to a given set of gains, that minimizes the time derivative of a quadratic Lyapunov function. This procedure eliminates the necessity of finding the membership function expressions to implement the control law, guarantees an H∞ performance and ensures that the state trajectory remains within a region in which the T–S fuzzy model is valid. Due to the H∞ control design, that frequently results in very large control inputs, it is considered that the switched control law is subject to actuator saturation. Finally, two examples are presented. The first example studies the control of a chaotic Lorenz system. It shows that, for disturbances with large magnitude, the proposed procedures provided better results than the obtained with another recent method found in the literature, that considers full access to the membership functions. In the second example, a practical implementation of an active nonlinear suspension control system, considering an uncertain bounded mass and a fault in the actuator, confirms the effectiveness of the proposed approach.
Keywords: Control of uncertain nonlinear systems; Control signal saturation; H∞ control; Linear matrix inequality (LMI); Local stability; Switched control; Takagi–Sugeno (T–S) fuzzy model